Plant Polyamines - Takahashi, Taku (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Polyamines are small organic compounds found in all living organisms. In recent years, there have been many exciting advances in our understanding of plant polyamines, such as the determination of the biosynthetic and catabolic pathways of plant polyamines and the identification of the roles that plant polyamines play in cellular processes. This Special Issue contains six original research papers and three review articles, providing valuable insights and information for future polyamine-related research.